Body morphometric measurements of Azakheli buffaloes: A neglected animal genetic resource of Pakistan - S. Rahman; I. Zahoor; R. Amjad; A. Basheer (Revista Científica)
The current study aims to morphologically characterize the Azakheli buffalo breed and develop phenotypic standards for this neglected animal genetic resource of Pakistan, which is present in some specific regions of the country’s northern areas. The body morphometric measurements of 220 adult (33 males and 187 females) animals were taken, in centimeters, for 26 different biometric parameters, including chest girth (CG), body length (BL), barrel depth (BD), height-at-withers (HW), hip height (HH), face length (FL), face width (FW), ear length (EL), ear width (EW), horn length (HL), horn circumference (HC), neck length (NL), neck width (NW), rump length (RL), rump width (RW), thurl width (TW), tail length (TL), tail circumference (TC), pin-bone distance (PBD), fore-teat length (FtL), fore-teat circumference (FtC), rear-teat length (RtL), rear-teat circumference (RtC), testes length (TesL), testes width (TesW), and scrotal circumference (SC) with the help of a measuring tape and scale. The data were subjected to descriptive and Pearson correlation analysis in R-studio. The values of mean plus- minus standard error for male morphometry were 183.43±1.140 (CG), 147.26±0.556 (BL), 69.85±0.523 (BD), 130.22±0.500 (HW), 125.60±0.558 (HH), 50.06±0.416 (FL), 24.38±0.325 (FW), 23.08±0.919 (EL), 16.10±0.289 (EW), 42.2402±0.957 (HL), 17.34±0.355 (HC), 55.93±0.403 (NL), 44.09±0.568 (NW), 42.59±0.309 (RL), 51.91±0.614 (RW), 46.83±0.708 (TW), 24.05±0.375 (PBD), 67.86±1.551 (TL), 17.19±0.292 (TC), 9.85±0.332 (TesL), 7.46±0.248 (TesW), and 19.32±0.584 (SC). Similarly, in females the values observed were 192.65±0.464 (CG), 145.89±0.424 (BL), 67.05±0.312 (BD), 129.41±0.353 (HW), 123.29±0.325 (HH), 49.63±0.279 (FL), 24.89±0.195 (FW), 23.87±0.266 (EL), 16.45±0.180 (EW), 46.58±0.523 (HL), 19.83±0.332 (HC), 57.25±0.325 (NL), 44.14±0.307 (NW), 43.02±0.261 (RL), 54.25±0.304 (RW), 49.58±0.363 (TW), 26.00±0.261 (PBD), 74.85±0.774 (TL), 17.14±0.254 (TC), 7.72±0.170 (FtL), 10.79±0.154 (RtL), 6.88±0.114 (FtC), 8.20±0.129 (RtC). The highest values of correlation coefficient observed were 0.893 for the FtL/FtC, 0.883 for the TesW/SC, 0.881 for the RtL/RtC, 0.856 for the FtL/RtL, 0.789 for the NL/ NW and RW/TW, 0.624 for the NW/RW, 0.612 for the CG/HH, and 0.599 for the HH/BL. It is suggested that these data would help identify this buffalo breed’s purebred animals for future breeding and selection programs.